Peralatan Inovasi Live-Line Maintenance : Temporary Cross Arm Support Insulator - Priyatno, Heru (ELECTRON Jurnal Ilmiah Teknik Elektro, 2023)
Live Line Maintenance (PDKB) Medium Voltage requires the right method to complete each type of live line maintenance working, as is the case for maintenance/replacement of support insulators and cross arms for double circuit construction on the top side. Temporary Cross Arm Support Insulator construction is intended to avoid blackouts to customers when maintenance work is carried out on Double Circuit construction. There is no method that can be used, maintenance or replacement of the Double Circuit Insulator construction still has to turn off the power grid. To overcome this problem, it is necessary to construct temporary equipment that is able to provide a solution by making a temporary Cross Arm Support Insulator. The construction design of this equipment can be used for replacement/maintenance of Double Circuit Supported Insulator construction. This equipment will be very helpful in carrying out network maintenance work and can be implemented in PLN's operational units, so that the implementation of work becomes safer, faster, more efficient and can avoid blackouts due to such maintenance. By not turning off the power grid, electrical energy can still be distributed.